SOCIO - ECONOMIC SURVEY IN BENGHAZI CITY AN EXPLORATORY STUDY - Mukerji , S.; Dutta , J. (Dirasat in Economics and Business, 1968)
Socio-economic Surveys have been found to be extremely useful in planning and in Social research. One distinct advantage of such surveys is that they furnish quantitative information on certain needs of the population in a relatively short time and at a nominal expenditure. Some countries have set up specific bodies for conducting sample surveys on a continued basis. For example, in India The National Sample survey, Indian Statistical Institute, which is a Semi - Government Organisation has been conducting detailed surveys since Indian Independence. In Libya a detailed survey, but on a limited scale was conducted in 1962 1. It is felt that similar studies with greater geographical coverage and extension over time would have been more useful. It is gratifying to learn that the Faculty of Economics and Commerce, of the University of Libya has a plan to conduct a sample survey within the city limits of Benghazi in near future. The present study is based on the data collected by some of the students of the fourth years class of the Department of Economics. The survey was primarily designed to give the students training in the various aspects of sample survey. This necessarily restricted both the Size of the sample and the questionnaire.